2017
DOI: 10.1186/s12864-017-4322-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Brevibacterium strains: insights into key genetic determinants involved in adaptation to the cheese habitat

Abstract: Background Brevibacterium strains are widely used for the manufacturing of surface-ripened cheeses, contributing to the breakdown of lipids and proteins and producing volatile sulfur compounds and red-orange pigments. The objective of the present study was to perform comparative genomic analyses in order to better understand the mechanisms involved in their ability to grow on the cheese surface and the differences between the strains.ResultsThe genomes of 23 Brevibacterium strains, including twelve strains iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 95 publications
2
38
0
Order By: Relevance
“…In other cases, they were microbes associated with human or other mammal bodies. Modern examples of the latter include the use of salivary microbial communities to initiate the fermenting process in chicha production in Peru, and similar fermented beverages around the world (Freire et al, 2016), the use of skin microbes to produce bodily aromas in some semi-soft cheeses (Pham et al, 2017), the use of body associated Lactobacillus species in sourdough breads (Gänzle and Ripari, 2016) or the use of the ancestrally mouth-associated bacteria species, Streptococcus thermophilus, in the production of yogurt (Goh et al, 2011). Once they began using body and other microbes to ferment foods, our ancestors extended their genomes and ultimately their phenotypes in much the way that beavers do in building a dam that yields a pond (Carthey et al, 2018).…”
Section: The Extended Microbiomementioning
confidence: 99%
“…In other cases, they were microbes associated with human or other mammal bodies. Modern examples of the latter include the use of salivary microbial communities to initiate the fermenting process in chicha production in Peru, and similar fermented beverages around the world (Freire et al, 2016), the use of skin microbes to produce bodily aromas in some semi-soft cheeses (Pham et al, 2017), the use of body associated Lactobacillus species in sourdough breads (Gänzle and Ripari, 2016) or the use of the ancestrally mouth-associated bacteria species, Streptococcus thermophilus, in the production of yogurt (Goh et al, 2011). Once they began using body and other microbes to ferment foods, our ancestors extended their genomes and ultimately their phenotypes in much the way that beavers do in building a dam that yields a pond (Carthey et al, 2018).…”
Section: The Extended Microbiomementioning
confidence: 99%
“…Another class of bacteriocin is represented by Linocin M18, initially characterized in Brevibacterium linens (Valdés‐Stauber and Scherer ) and recently detected in 15 of the 23 investigated B. linens genomes belonging to different phylogenetic groups and isolated from different habitats (Pham et al . ). The authors also concluded that the main function of Linocin M18 in cheese is to inhibit other microbial groups that share the same ecological niche, therefore conferring a selective advantage on themselves.…”
Section: Introductionmentioning
confidence: 97%
“…The taxonomy of the genus Brevibacterium is under reorganization with Brevibacterium genomes varying greatly in both size and functional content 7,14,15 . It should be noted that the genus Brevibacterium also contains opportunistic pathogens and other biotechnologically important species 1619 .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the genus Brevibacterium also contains opportunistic pathogens and other biotechnologically important species 1619 . Cheese-associated subtypes of Brevibacterium can be found in several species of the genus, suggesting that adaptation to cheese environments might have been acquired independently through horizontal gene transfer (HGT) events 15,20 . Two recent studies have analyzed the genetic content of Brevibacterium focusing on their putative genetic functions in cheese production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation